Occurrence of Trace and Toxic metals in River Narmada - Mohammed Arif; Dr Jakir Hussain; Dr Ikbal Hussain (EQA, 2014)
Deteriorating water quality has become a serious problem in developing countries. Almost 70% of Indian’s surface water resources have become contaminated due to the discharge of untreated sewage and industrial effluents. The results reveals that out of nine water quality stations monitored, water samples collected at 5 water quality stations (Amarkantak, Dindori, Manot, Barmanghat and Handia) are found to be within the permissible limit for all purposes in respect to trace & toxic metals. While Sandia, Hoshangabad, Mandleshwar and Garudeshwar stations were beyond the permissible limit due to presence of chromium, copper and iron metals. The major source of pollution to the Narmada river is the anthropogenic municipal solid waste and sewage from nearby towns/habitations, agricultural runoff and native soil erosion. The quality of the Narmada River is degraded due to the municipal and industrial discharges from the catchment.